THE MATHEMATICAL MODEL OF THE PHOTOMETRIC VARIABILITY AND CLASSIFICATION OF SEMIREGULAR PULSATING ASYMPTOTIC GIANTS BRANCH STARS - Kudashkina, L. S. (Одеські астрономічні публікації, 2012)
The modern review of the stars which are located at the position of asymptotic giant branch at the HRdiagram is presented. The most interesting problems connected to these objects are noted, as well as attention is paid to classification and to the evolutionary status. We provided mathematical modeling of the mean light curve of the semiregular supergiant S Per. It is shown, that by means of the periodogram analysis, it is possible to determine the period of the main variability and to provide further detailed classification of semiregular pulsating stars, approximating their mean light curves with a trigonometric polynomial. It is offered to use the photometric period for estimates of physical parameters of pulsing stars.